HLA Association with Drug-Induced Adverse Reactions. (23rd November 2017) - Fan, Wen-Lang; Shiao, Meng-Shin; Hui, Rosaline Chung-Yee; Su, Shih-Chi; Wang, Chuang-Wei; Chang, Ya-Ching; Chung, Wen-Hung
Abstract : Adverse drug reactions (ADRs) remain a common and major problem in healthcare. Severe cutaneous adverse drug reactions (SCARs), such as Stevens–Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) with mortality rate ranges from 10% to more than 30%, can be life threatening. A number of recent studies demonstrated that ADRs possess strong genetic predisposition. ADRs induced by several drugs have been shown to have significant associations with specific alleles of human leukocyte antigen (HLA) genes. For example, hypersensitivity to abacavir, a drug used for treating of human immunodeficiency virus (HIV) infection, has been proposed to be associated with allele 57:01 of HLA-B gene (terms HLA-B ∗ 57:01 ). The incidences of abacavir hypersensitivity are much higher in Caucasians compared to other populations due to various allele frequencies in different ethnic populations. The antithyroid drug- (ATDs- ) induced agranulocytosis are strongly associated with two alleles: HLA-B ∗ 38:02 and HLA-DRB1 ∗ 08:03 . In addition, HLA-B ∗ 15:02 allele was reported to be related to carbamazepine-induced SJS/TEN, and HLA-B ∗ 57:01 in abacavir hypersensitivity and flucloxacillin induced drug-induced liver injury (DILI). In this review, we summarized the alleles of HLA genes which have been proposed to have association with ADRs caused by different drugs.